Complexo de cobre(II), 1,10-fenantrolina e L-glutamina: síntese, caracterização físico-química e análise da viabilidade celular em linhas celulares tumorais e não tumorais - SOUZA JUNIOR, Marinaldo Vilar de (2023)
Despite the scientific advancements in the search for improvements in the pharmacological properties of copper coordination complexes, which can be used in cancer chemotherapy, there are still open questions such as the selectivity of the complex, treatment resistance, toxicity, and mechanisms of action. Considering this fact, the synthesis of coordinated copper(II) complexes emerges as a promising alternative, due to their multifunctional biological effects. Based on this motivation, in this work, the synthesis of a ternary copper(II) complex with 1,10-phenanthroline and L-glutamine was performed using the slow evaporation method, and the study of its structural, vibrational, thermal, solubility, and cytotoxic properties was carried out, aiming for a possible application as an antitumor agent. To achieve the desired physical characterization, UV Vis spectroscopy was used to determine the pH of crystal complexation, X-ray diffraction (XRD) was used to verify its crystalline phase, infrared (IR) and Raman spectroscopies were employed to obtain its vibrational properties, and thermal analysis techniques (thermogravimetry (TG), differential thermal analysis (DTA), and differential scanning calorimetry (DSC)) were used to evaluate its stability at high temperatures. Through UV Vis spectroscopy analysis, the complexation pH was found to be 4.3. XRD analysis revealed that the complex crystallizes in the triclinic system, with space group P1 ̅ (Ci 1), obtaining the following lattice parameters: a = 7.0402 (11) Å, b = 12.3123 (2) Å, c = 12.8992 (2) Å, α = 110.512 (7)º, β = 105.037 (7)º, γ = 97.373 (7)º with volume 981.2 Å3. IR and Raman spectra showed characteristic vibrations originating from the metal complexation to the organic molecules. According to the thermal analysis, it was possible to observe that the crystals undergo a phase transformation due to the loss of water molecules. XRD as a function of temperature corroborated the phase transformation observed via thermal analysis, as diffraction patterns underwent changes, indicating that the coordination complex may have undergone conformational changes adopting a new phase within the monoclinic system. In addition, quantum chemistry calculations were performed to obtain an understanding of the relationship between the electronic properties and the reactivity of the metal complex, as well as to corroborate the experimental spectroscopic results. Finally, cytotoxic assays (in vitro) with PC-3 (IC50 = 3,3 μM) and SNB-19 (IC50 = 3,8 μM) cancer cells were carried out to investigate the antitumor potential of the complex.